Membawa Lari Perempuan dalam Perspektif Hukum Pidana - Muhamamad Natsir (Jurnal Litigasi Amsir, 2022)
This study aims to determine the application of the provisions of material criminal law to the crime of taking women away in the Unaaha District Court Decision Number 14/Pid.B/2011?PN.Unh and to find out the legal considerations in imposing criminal sanctions on the perpetrators of the crime of taking women away in the decision. Unaaha District Court Number 14/Pid.B/2011?PN.Unh. This research was conducted at the Unaaha District Court. The data collection method used was the library method and the interview method, and then the data obtained were analyzed qualitatively. The results showed that (1) the application of the provisions of the material criminal law against the crime of taking women away in the Unaaha District Court Decision Number 14/Pid.B/2011?PN. Unaha, the prosecutor should not only apply Article 332 paragraph 1 of the Criminal Code in making the indictment but also applies Article 81 of Law Number 23 of 2002 concerning Child Protection. (2) Legal considerations in imposing criminal sanctions on perpetrators of the crime of taking women away in the decision of the Unaaha District Court Number 14/Pid.B/2011?PN.Unh, the judge should have sentenced not only 10 (ten) months in prison if it was based on the minimum criminal limit prison as regulated in Article 81 of Law Number 23 of 2002 concerning Child Protection.